Neural networks for robotics an engineering perspective - Arana-Daniel, Nancy; Lopez-Franco, Carlos; Alanis, Alma Y. (CRC Press, Taylor & Francis Group, 2019)
The book offers the reader the insight on artificial neural networks for giving a robot a high level of autonomy tasks such as navigation, object recognition, and clustering, with real-time implementations. The reader will learn various methodologies that can be used to solve each stage on autonomous navigation for robots, from object recognition, clustering of obstacles, cost mapping of environments, path planning, and vision to low level control.